Penyuluhan Bahaya Malware Dan Spiware Dalam Penggunaan Internet Bagi Sekolah - Victor Victor; Hamjah Arrahman; Vera Wijaya; Tony honkly; Rozi Rozi; Niki Niki; Fadya Fadya (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
In accordance with the title of this community service program "Digital Video Editing Training for Youtube Publishing in the Tanjung Mulia Hilir Village Community". Skills training activities are supported by lectures, questions and answers and of course direct practice in the computer laboratory. Training modules will be provided to participants as a tool for practical activities in the laboratory. The aim of implementing this community service program is to improve students' skills in using the internet and the benefits and activities that can be carried out using the internet, so that it can increase students' creativity in using the internet, especially to have a positive impact on internet use for students. This form of training is a very effective form of providing refreshment and additional insight and new knowledge in the field of information technology outside of the learning process received at each school.